Simulation of ATMEGA8 Microcontroller-Based Schizophrenia Patient Detector - Loniza, Erika; Utami, Anugrah; Safitri, Meilia; Ermawati, Yuli (Universitas Muhammadiyah Yogyakarta, 2020)
Schizophrenia is a chronic mental disorder causing sufferers experiencing delusions, hallucinations, thoughts distracting, and behavior changing. This condition that usually lasts a long time is often interpreted as a mental disorder, given the difficulty of the patient to distinguish between reality and one's mind. The purpose of this study is to facilitate nurses when doing care, especially in the inpatient room, and so that care is more intensive. By using the magnetic sensor as a detector when the door is open, and the PIR (Passive Infrared Receiver) sensor as a detection of the patients flew motion, and the lamp as an indicator. The results of the data can be obtained from testing by calculating the distance if the sensor can detect. The testing results the device it is proven that the magnetic sensor can detect up to 1 cm, and the PIR sensor can detect up to 5,5 meters.